The Analysis of The Smooth Transport of Goods and Tourism at The Region of Lake Toba - Budi Santoso Sitorus; Christina Natalia Sitorus; Tulus Irpan Harsono Sitorus (Jurnal Logistik Indonesia, 2022)
The results of the study found there are still many violations due to the transport of goods exceeds its capacity in some Districts and Cities , there is still limited services urban transport in the province of North Sumatra, which connects the city/district, yet connected between the node of transport in the region of Lake Toba surrounding and the conditions of a transportation node in the District within the region of Lake Toba has not been satisfactory, which lead to high cost of transportation so that people prefer to use a personal vehicle or rental vehicle. Research methodology using qualitative research method with the technique of collecting secondary data sourced from the literature and the study of literature. Analysis of research using a policy analysis that as the initial hypothesis and the consequences can be foreseen. Analysis of the cost is the cost incurred from travel and descriptive Analysis is a method used to describe the transport network for the transport of goods from the industry and/or economic zones to the port through the toll road Medan-Binjai and Medan-Tebing tinggi, as well as tourism services in the area of Toba Lake around, do the analysis of the network of urban transport in the Province of North Sumatra. The analysis of the problem tree is used describe the problem of causal relationships.